2016
DOI: 10.1038/srep35764
|View full text |Cite
|
Sign up to set email alerts
|

Study to explore the mechanism to form inclusion complexes of β-cyclodextrin with vitamin molecules

Abstract: Host–guest inclusion complexes of β-cyclodextrin with two vitamins viz., nicotinic acid and ascorbic acid in aqueous medium have been explored by reliable spectroscopic, physicochemical and calorimetric methods as stabilizer, carrier and regulatory releaser of the guest molecules. Job’s plots have been drawn by UV-visible spectroscopy to confirm the 1:1 stoichiometry of the host-guest assembly. Stereo-chemical nature of the inclusion complexes has been explained by 2D NMR spectroscopy. Surface tension and cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
118
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 61 publications
8
118
0
1
Order By: Relevance
“…It has been found that γ values, in both the cases, was increasing with increasing concentration of CDs and (Figure ), may be due to the insertion of the IL molecule inside the CD cavity from the bulk forming inclusion complexes. (Figure 8) . Also at a certain concentration of CD a sudden break point arrived and after that the curve becomes almost flattened (Figure ).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…It has been found that γ values, in both the cases, was increasing with increasing concentration of CDs and (Figure ), may be due to the insertion of the IL molecule inside the CD cavity from the bulk forming inclusion complexes. (Figure 8) . Also at a certain concentration of CD a sudden break point arrived and after that the curve becomes almost flattened (Figure ).…”
Section: Resultsmentioning
confidence: 85%
“…Study of UV‐Vis spectroscopy is a strong tool to calculate the association constant ( K a ) for the formation of ICs . In the host guest inclusion complexation when the ILs (act as chromophore) is encapsulated in the cavity of CD from the comparatively more polar bulk, there occurs a change of the molar extinction coefficient (Δϵ) of the IL .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Corresponding to their molecular structure and shape, they acquire a unique ability of entrapping guest molecules in their internal cavity. As a result, a host‐guest complex is formed between cyclodextrins and guest molecules ,. Among the mentioned cyclodextrins, β‐CD is the most widely used as they are easily accessible due to its appropriate internal cavity diameter and high water‐solubility .…”
Section: Introductionmentioning
confidence: 99%